OPTIMIZING PROJECT SCHEDULING USING CPM AND PERT METHODS (CASE STUDY: PEJAMBON 8-STOREY FLAT, CENTRAL JAKARTA) - Dewi Fauzah; Rafiq Setyawan; Anasya Arsita Laksmi; Sigit Adi Soebakti (Jurnal Ilmiah Teknik Sipil, 2024)
Pejambon 8 Storey-Flat Construction Project is one of the annual work programs through the allocation of Government Islamic Securities (SBSN) funding for the 2023 Ministry of Finance of the Republic of Indonesia. In this research, the CPM and PERT planning methods were used to implement project time management and increase effectiveness, by making schedules empirically. The aim of applying the CPM and PERT methods is to compare expectations with actual progress and avoid delays in critical path activities so that it can shorten the project period by considering costs. This research used the PERT and CPM method approach in evaluating projects. This method begins with compiling a project network diagram and collecting information related to time variations that can occur on projects in the field. Some of the results of the processed data produced are information related to the critical path of the project, probability of project scheduling, and variations in operational costs according to the total duration of work. The data required in this research include the physical progress report of the project, Project Implementation Schedule, Curve S, and RAB.